(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The article presents a challenge to the History high schools’ curriculum by depicting that among the secondary concepts currently used in the understanding of History in high schools in South Africa the socio-environmental concept has been ignored which poses a question of whether or not the high school History curriculum is complete. According to Jared Diamond, societies collapse due to diverse reasons but environment is key. Hence D Woster, W Cronon and N Jacobs argue that the environment does not just represent a historical backdrop, but is an agent in its own right, providing a “material base for the power to dominate others” as well as the “power to endure domination”. The case study of forced removals from Lady Selborne in 1961 and resettlement in Ga-Rankuwa in Pretoria demonstrates that forced removals from Lady Selborne did not only result in people losing their historical lands, material possessions, homes, history and their sense of being and connectedness but they also lost their attachment to their inheritance – the environment which resulted in their being apathetic towards environmental issues. Thus, the article proposes the inclusion of socio-environmental concepts in history which will provide a crucial step in terms of inculcating environmental activism and ethics among the youth of South Africa.